2001
DOI: 10.1081/jdi-100103491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Improvement by Increased Frequency of on-Line Hemodialfiltration

Abstract: On-line HDF offers a better cardiovascular stability and clinical improvement. Thrice weekly on-line HDF offers a significant benefit when compared with lower frequencies of HDF per week and high-flux HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
3
33
1
1
Order By: Relevance
“…But, this study included a small number of patients (about twenty per group). Lin (2001) showed that patients on HDF (online post dilution) had significantly higher physical well-being score compared with high-flux HD. In this study, patients scored their physical conditions such as subjective well-being, work tolerance, and mental alertness weekly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But, this study included a small number of patients (about twenty per group). Lin (2001) showed that patients on HDF (online post dilution) had significantly higher physical well-being score compared with high-flux HD. In this study, patients scored their physical conditions such as subjective well-being, work tolerance, and mental alertness weekly.…”
Section: Discussionmentioning
confidence: 99%
“…All patients are dialyzed on biocompatible polysulfone membrane. 20 Also, Schiffl 21 found that HDF was associated with partial improvement of quality of life. Additional tests also showed that there were no statistically significant differences in SF-36 domains between high-flux HD and low-flux HD in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One single-center RCT (n538 in the HDF group) reported better self-reported physical wellbeing compared with high-flux HD using a self-developed HRQOL instrument (15), whereas another single-center randomized trial (n524 in the hemodiafiltration group) reported no difference in physical functioning using the Kidney Disease Questionnaire (16). Considering the findings of this much larger multicenter randomized trial, it seems safe to agree with the authors that HDF is unlikely to improve HRQOL in a substantive manner.…”
mentioning
confidence: 99%